Enhancement of low-temperature thermoelectric performance via Pb doping in Cu3SbSe4. (April 2023) - Pal, Anand; Shyam Prasad, K.; Gurukrishna, K.; Mangavati, Suraj; Poornesh, P.; Rao, Ashok; Chung, Yin-Chun; Kuo, Y.K.
Abstract: We investigated the synthesis protocols of the pure and Pb-doped bulk polycrystalline Cu3 Sb1- x Pb x Se4 (0 ≤ x ≤ 0.04) system and studied their crystallographic and thermoelectric properties intending to reach a high figure of merit (ZT). The solid-state reaction method under a 10 −5 Torr vacuum was employed to synthesize the pristine and doped samples. The Rietveld analysis of room-temperature X-ray diffraction confirmed tetragonal structure with space group I 4 ‾ 2 m for all studied compositions. The electrical resistivity [ ρ ( T )] demonstrated a degenerate semiconducting behavior for pure as well as doped samples. The overall ρ ( T ) increased with increasing Pb content. The positive values of Seebeck coefficient [ S ( T )] data in the investigated temperature range for all the studied compositions revealed that holes played a major role in the conduction mechanism. The S ( T ) values rose with increased temperature, a characteristic of degenerate semiconductors. The temperature-dependent Seebeck coefficient data analysis revealed a narrow bandgap behavior for all studied samples. The analysis suggests that the electronic thermal conductivity only contributed up to 1% to the total thermal conductivity, and the remaining 99% was contributed by lattice thermal conductivity. The estimated ZT values showed as much as 20% enhancement at 380 K for a 1% doped s ample, Cu3 Sb0.99 Pb0.01 Se4 . The thermoelectric compatibility factor decreased with doping, and a maximum value (1.14 V −1 ) was found for the pristine sample at 250 K. Graphical abstract: Image 1 Highlights: Rietveld refinement analysis confirms the phase purity of all the samples. About 15% reduction in thermal conductivity is achieved by 2% substitution of Sb by Pb. About 30% enhancement of power factor and 20% in figure of merit (ZT) through 1% substitution of Sb by Pb. The highest compatibility factor is observed for the pristine sample at 250 K.